Endothelial Dysfunction and Coronary Vasoreactivity - A Review of the History, Physiology, Diagnostic Techniques, and Clinical Relevance - Gunawardena, Tharusha; Merinopoulos, Ioannis; Wickramarachchi, Upul; Vassiliou, Vassilios; Eccleshall, Simon (Current Cardiology Reviews, 2021)
The fervency for advancement and evolution in percutaneous coronary intervention has revolutionised the treatment of coronary artery disease. Historically, the focus of the interventional cardiologist was directed at the restoration of luminal patency of the major epicardial coronary arteries, yet whilst this approach is evolving with much greater utilisation of physiological assessment, it often neglects consideration of the role of the coronary microcirculation, which has been shown to clearly influence prognosis. In this review, we explore the narrative of the coronary circulation as more than just a simple conduit for blood but an organ with functional significance. We review organisation and physiology of the coronary circulation, as well as the current methods and techniques used to examine it. We discuss the studies exploring coronary artery endothelial function, appreciating that coronary artery disease occurs on a spectrum of disorder and that percutaneous coronary intervention has a latent effect on the coronary circulation with long-term consequences. It is concluded that greater recognition of the coronary artery endothelium and mechanisms of the coronary circulation should further guide revascularisation strategies.
Keywords: vasomotion